Music in me a program of music activities and culminating concert for special education children - Matsuura, Sara T. (Quezon City College of Music, University of the Philippines Diliman, 2016)
The project is a program of music activities designed for special children. It aims to utilize music as an avenue to help select high school students under the mainstream/special education program. Specifically, it aims to create a compilation of music activities designed to improve the student's psychomotor skills, interpersonal and intrapersonal behavior, in hopes that it may help the students in their social encounters and career opportunities in the future.
Undergraduate student project (B.M. Music Education) -- University of the Philippines Diliman.